Anisotropy of elastic properties and thermal conductivity of the upper mantle -- a case study of xenoliths shape: Evidence from xenoliths in basalts in North Eurasia - Grachev A.F. (Федеральное государственное бюджетное учреждение науки Геофизический центр Российской академии наук, 2016)
The paper presents data on relations between the petrofabrics of olivine crystals, elastic properties and thermal conductivity of mantle xenoliths in basalts from the Bohemian Massif, Pannonian Basin, Baikal Rift, and Lanzarote Island (Canary Islands). The sizes of the xenoliths themselves and olivine porphyroblasts and neoblasts in them were proved to be distributed according to the lognormal law. The identified seismic anisotropy of the xenoliths is controlled by the preferred orientation of the axis [100] of the olivine and partial melting zones in the xenoliths. The axes of the maximum shortening of the samples coincide with the dominant distribution mode of the axes [010] of olivine crystals. The major maxima of the axes [001] are parallel to the long axes of the xenoliths, whereas the maxima of [100] plot along the middle axis of the samples. The elastic properties $(V_p)$ and thermal conductivity ($\lambda$) of mantle xenoliths are controlled by parameters of the crystal lattice of olivine and the orientation of partial melting zones, which are correlated with the orientation of the long, middle, and short axes of the xenoliths. These data imply that the geometrically regular shapes of mantle xenoliths had been in situ formed in the mantle before these xenoliths were entrained by melts and brought to the surface.
Keywords: SEISMIC ANISOTROPY OF THE MANTLE; XENOLITHS IN BASALT; PARTIAL MELTING; ELASTIC PROPERTIES; THERMAL CONDUCTIVITY